A non-silicon-based porous adsorption and catalysis coupling material and a preparation method thereof
Patent Information
- Application Number
- CN202610828417.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-09
AI Technical Summary
[0004]本发明旨在提供一种非硅基多孔吸附-催化耦合材料及其制备方法,以解决现有废弃油脂处理过程中含硅污染物难以高效脱除、易导致主催化剂中毒以及传统吸附材料自身含硅可能带来二次污染的技术问题
[0043] This invention can efficiently and selectively remove silicon-containing contaminants from waste oils. By controlling the mesopore size of the main material within a suitable range to match the size of silicon-containing contaminants such as siloxanes, silicone greases, and clay particles, and by combining the synergistic effect of weak acid and weak base sites on the material surface with the chemical affinity of the functional modification layer, highly selective adsorption and catalytic cracking of silicon-containing contaminants are achieved, resulting in a desilication effect superior to existing conventional treatment methods.
Smart Images

Figure CN122377414B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste oil purification and treatment, specifically to a non-silicon-based porous adsorption-catalytic coupling material and its preparation method. Background Technology
[0002] Waste oils are important renewable raw materials for the production of biodiesel, industrial oleic acid, and fatty acid methyl esters. Common waste oils include kitchen waste oil and acidified oil. However, these oils often contain various silicon-containing contaminants, mainly from three sources: first, siloxanes from defoamers; second, silicone grease from mechanical lubricants and container release agents; and third, particulate matter remaining from activated clay during oil refining, which is a silicate mineral. These silicon-containing impurities can deposit on the surface of precious metal catalysts or acid / alkaline catalysts during subsequent catalytic conversion processes such as esterification, transesterification, or hydrogenation, leading to permanent catalyst poisoning and deactivation, and severely affecting the purity of the final product.
[0003] Current treatment methods, such as distillation, solvent extraction, and adsorption with ordinary activated clay, generally suffer from low desilication efficiency, poor selectivity, easy introduction of secondary pollution, and high operating costs. Therefore, it is necessary to develop a new type of functional material that possesses highly selective adsorption or catalytic cracking capabilities for silicon-containing pollutants, and is silicon-free itself to avoid cross-contamination of the treatment system. Summary of the Invention
[0004] The present invention aims to provide a non-silicon-based porous adsorption-catalysis coupling material and its preparation method, in order to solve the technical problems of the difficulty in efficiently removing silicon-containing pollutants in the existing waste oil treatment process, the easy poisoning of the main catalyst, and the secondary pollution that may be caused by the silicon content of traditional adsorption materials themselves.
[0005] A non-silicon-based porous adsorption-catalysis coupling material includes: a non-silicon-based host material and a functional modification layer;
[0006] a) The non-silicon-based host material is a product of calcination of γ-Al2O3 and magnesium aluminum hydrotalcite; and the surface of the host material has both weak acidic sites and weak basic sites, the weak basic sites of which can promote the hydrolysis of silicon ester compounds.
[0007] The non-silicon-based host material has a predominantly mesoporous pore structure with a pore size ranging from 5 nm to 20 nm and a specific surface area ≥ 200 m². 2 / g, pore volume ≥0.3 cm³ 3 / g;
[0008] The weakly acidic sites on the surface of the main material originate from the coordinated unsaturated Al in γ-Al2O3 and the calcination products of magnesium aluminum hydrotalcite. 3+And the interaction between surface Al-OH, surface aluminum ions and hydroxyl groups, the coordinated unsaturated Al 3+ It is a Lewis acid, the surface Al-OH, the interaction between surface aluminum ions and hydroxyl groups is a Brønsted acid; the weakly basic sites originate from Al - O - Mg-OH and O at oxygen vacancies 2- Species;
[0009] b) A functional modification layer located on the surface and within the pores of the host material, wherein the functional modification layer is a modification component containing one of an organic amine compound, a phosphate group, and a metal ion, and wherein the functional modification layer is free of silicon;
[0010] Wherein, the organic amine compound is a non-silane organic amine, the phosphate group is derived from non-silicon phosphates, and the metal ion is a non-silicon metal ion.
[0011] A method for preparing a non-silicon-based porous adsorption-catalytic coupling material includes the following steps:
[0012] S1: Preparation of the host material γ-Al2O3
[0013] S11. Sol preparation
[0014] Accurately weigh out BASF Pluronic P123 template agent, dissolve it in anhydrous ethanol, and stir at room temperature until completely dissolved.
[0015] Add concentrated nitric acid (65 wt%) dropwise, stirring until the solution is homogeneous. Add aluminum isopropoxide, aluminum nitrate, or aluminum sulfate to the solution and continue stirring at room temperature to form a clear and transparent sol.
[0016] The preparation process involves controlling the temperature at 25-30℃ and the stirring speed at 300-400 rpm to ensure that the template agent, acid, and aluminum source come into full contact and form a uniform sol system.
[0017] S12. Sol aging
[0018] The obtained transparent sol was transferred into an oven and evaporated at a constant temperature of 40-80℃ for 24-48 h to form a gel for 12-24 h, thus completely removing the residual solvent.
[0019] S13. Firing and shaping
[0020] The dried raw powder was placed in a muffle furnace and heated at a rate of 1-5 °C / min in an air atmosphere. It was held at 250 °C for 2 h and at 500 °C for 4 h. After calcination, it was naturally cooled to room temperature to obtain a white mesoporous γ-Al2O3 main material.
[0021] S2. Preparation of the main material, magnesium aluminum hydrotalcite.
[0022] S21. Preparation of precursor solution
[0023] Accurately weigh Mg(NO3)2·6H2O and Al(NO3)3·9H2O, mix them in a Mg / Al molar ratio of 3:1, dissolve them in deionized water, and prepare a mixed salt solution with a total metal ion concentration of 1.0 mol / L. Precipitant solution: Dissolve NaOH and Na2CO3 in deionized water to make the NaOH concentration 2.0 mol / L and the Na2CO3 concentration 0.5 mol / L.
[0024] S22. Magnesium-aluminum hydroplaning synthesis reaction
[0025] Under a 60℃ water bath and 600rpm stirring, the metal salt solution and precipitant solution were added dropwise in parallel to the reaction vessel at a rate of 1.5 mL / min. The dropping rate was controlled by a micro-injection pump to strictly maintain the pH of the mixed solution at 10±0.2. After the addition was complete, the slurry was transferred to a stainless steel high-pressure reactor and statically crystallized at 120℃ for 24 h.
[0026] S23. Crystallization washing
[0027] After crystallization, the solution was cooled to room temperature, centrifuged to separate the precipitate, and repeatedly washed with deionized water until the pH of the filtrate reached 7. The precipitate was then washed once with anhydrous ethanol. The precipitate was dried in an oven at 80°C for 12 h to obtain the magnesium aluminum hydrotalcite precursor.
[0028] S3. Main material firing and molding
[0029] 1-5 parts of the prepared γ-Al₂O₃ and 3-7 parts of magnesium aluminum hydrotalcite were mixed and placed in a muffle furnace. The mixture was heated to 550℃ at a heating rate of 2℃ / min and calcined in air for 4 h. After natural cooling, Mg(Al)O composite metal oxide was obtained. The specific surface area was measured to be ≥250 m². 2 The pore size is mainly distributed in the range of 5–15 nm; the density of weakly basic sites is 0.45–0.50 mmol / g, and the density of weakly acidic sites is 0.3–0.6 mmol / g.
[0030] S4: Functional Modification
[0031] Functional modifications are categorized into organic amine modifications, phosphate modifications, and metal ion modifications.
[0032] S41. Organic amine modification: The main material is dispersed in an anhydrous ethanol solution of organic amine, refluxed and stirred at 60-80℃ for 6-12 h, and then filtered, washed and dried;
[0033] S42. Phosphate modification: The material is immersed in a 0.1-1 mol / L phosphoric acid solution, stirred at room temperature for 2-6 h, dried, and then heat-treated at 200-300℃.
[0034] S43. Metal ion modification: The precursor solution is impregnated onto the host material using an equal-volume impregnation method, then allowed to stand, dried, and calcined at 400–500°C.
[0035] S5: Activation treatment
[0036] The S4-modified material was activated in an inert gas at 300–500 °C for 1–4 hours to obtain the non-silicon-based porous adsorption-catalytic coupling material.
[0037] The S2-modified material was activated in an inert gas at 300–500 °C for 1–4 hours to obtain the non-silicon-based porous adsorption-catalytic coupling material.
[0038] Preferably, the S1 wet chemical method employs one of the following methods: sol-gel method, hydrothermal method, and template method.
[0039] Preferably, in S2, the phosphoric acid solution is phosphoric acid or ammonium phosphate solution.
[0040] Preferably, in step S2, the precursor solution is Fe. 3+ Salt solution, Zr 4+ A type of salt solution, nitrate solution, and chloride solution.
[0041] Preferably, in step S3, the oven temperature is 60-100°C, and the inert atmosphere is either nitrogen or argon.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] This invention can efficiently and selectively remove silicon-containing contaminants from waste oils. By controlling the mesopore size of the main material within a suitable range to match the size of silicon-containing contaminants such as siloxanes, silicone greases, and clay particles, and by combining the synergistic effect of weak acid and weak base sites on the material surface with the chemical affinity of the functional modification layer, highly selective adsorption and catalytic cracking of silicon-containing contaminants are achieved, resulting in a desilication effect superior to existing conventional treatment methods.
[0044] This invention avoids secondary silicon contamination. Commonly used adsorbents in existing technologies, such as activated clay and silica gel, contain silicon, which can easily introduce new silicon contamination into the oils during processing. The main material of this invention is a non-silicon-based material, and the functional modification layer is also silicon-free, thus eliminating secondary contamination at the source and making it suitable for catalytic conversion systems sensitive to silicon impurities.
[0045] This invention achieves the coupling of adsorption and catalysis, enabling the irreversible removal of silicon-containing contaminants. The material not only physically adsorbs silicon-containing contaminants through its mesoporous structure, but also catalyzes the hydrolysis of silicon ester compounds or promotes the breaking of silicon-oxygen bonds through the weakly basic sites on the surface of the host material and the chemical activity of the modification layer. The silicate ions generated by hydrolysis are fixed in situ by functional groups or metal ions within the pores, preventing them from re-entering the liquid phase, thereby achieving the irreversible removal of silicon-containing contaminants.
[0046] This invention can significantly protect downstream main catalysts and extend their service life. The oils purified by this material can be directly used for subsequent catalytic reactions such as transesterification, hydrogenation, or esterification. Due to the significantly reduced silicon content in the oils, the problem of catalyst poisoning and failure caused by silicon deposition is effectively alleviated, and the service life of the main catalyst is significantly extended compared to using untreated oils.
[0047] The material of this invention possesses excellent renewability. After adsorption saturation, the material can be washed with an alkaline solution to desorb silicate ions, and then reactivated for reuse. Even after multiple regenerations, the desilication efficiency and main structure of the material remain stable, demonstrating good recyclability.
[0048] In summary, compared with existing technologies such as activated clay, silica gel, or ordinary desilication agents, this invention represents a substantial improvement in desilication efficiency, avoidance of secondary silicon contamination, protection of downstream catalysts, and renewability, and can meet the industrial demand for efficient purification of waste oils. Attached Figure Description
[0049] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation
[0050] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0051] Example 1: Performance comparison of γ-Al2O3 with different pore sizes prepared according to the present invention
[0052] γ-Al₂O₃ host materials with average pore sizes of 3 nm, 8 nm, 15 nm, and 25 nm were prepared by adjusting the amount of template agent P to 0.5 wt%, 3 wt%, 8 wt%, and 12 wt%, respectively, while maintaining a specific surface area of ~300 m². 2 / g, pore volume 0.4~0.6 cm³ 3 / g, all using "organic amine + phosphate + Fe 3+"Triple modification to treat kitchen waste oil containing 100 ppm of siloxanes and silicone esters, under the following conditions: 150℃, 2 h, 5 wt% addition."
[0053]
[0054] The results show that the pore size of 5–20 nm is the key range for obtaining high desilication efficiency, with 8–15 nm being the preferred range.
[0055] Example 2: Performance Comparison of Magnesium Aluminum Hydrotalcite Prepared by the Present Invention
[0056] Using MgAl hydrotalcite as the main component (Mg / Al molar ratios of 1:1, 2:1, 3:1, and 5:1), samples with weakly basic site densities of 0.05, 0.22, 0.48, and 0.72 mmol / g were obtained by adjusting the precipitation pH and calcination temperature. After all samples underwent the same triple modification, the silicone ester content in the treated ester-silicone ester wastewater model was 100 ppm, the aqueous phase pH was approximately 6, and the reaction conditions were 100℃ for 1 h.
[0057]
[0058] The results show that a weakly basic site density in the range of 0.1–0.5 mmol / g can both efficiently catalyze hydrolysis and prevent excessive dissolution of silicate ions; when the density is too high, the stability of silicate ions decreases, and some are released back into the liquid phase.
[0059] Example 3: Evaluation of γ-Al2O3 modified by the present invention
[0060] The γ-Al₂O₃ prepared using methods 1-3 was used to prepare a support for different types of modification according to the calcination scheme of this invention:
[0061]
[0062] Waste oil containing 100 ppm of silicon was treated under the same conditions: temperature 150℃, time 2 h.
[0063]
[0064] The results showed that the triple modification achieved a synergistic effect of "catalytic hydrolysis → chemical fixation → physical retention", and the desilication rate was significantly increased to 92%, which had a significant effect but did not reach the ideal effect.
[0065] Example 4: Evaluation of the modification of the magnesium aluminum hydrotalcite carrier prepared in this invention
[0066] The carriers prepared using methods 2-3 were modified in different ways according to the calcination scheme of this invention:
[0067]
[0068] Waste oil containing 100 ppm of silicon was treated under the same conditions: temperature 150℃, time 2 h.
[0069]
[0070] The results showed that the triple modification achieved a synergistic effect of "catalytic hydrolysis → chemical fixation → physical retention", and the desilication rate was significantly increased to 95%.
[0071] Example 5: Negative Effects of Functionality Modification Load Optimization and Over-Modification
[0072] Using γ-Al2O3 and magnesium aluminum hydrotalcite prepared in this invention as the main components, the following modifications were made:
[0073] (A) PEI loading: 0, 2, 5, 10, 15, 20 wt%
[0074] (B) Phosphate loading: 0, 0.5, 1.5, 3.0, 5.0, 7.0 mmol / g;
[0075] (C)Fe 3+ Loading capacity: 0, 2, 5, 8, 12 wt%.
[0076] With other modification conditions fixed at their optimal values, the removal rates of siloxane model oils by individual modification systems were tested, and the results are as follows:
[0077]
[0078] Excessive modification of PEI > 15 wt%, phosphate > 5 mmol / g, Fe 3+ >10 wt% leads to a 30-45% decrease in BET pore volume, hindering mass transfer and causing a decrease in desilication rate instead of an increase. Preferred range: organic amine 2-10 wt%, phosphate 0.5-3 mmol / g, Fe 3+ 2–8 wt%.
[0079] Example 6 (Comparative Experiment): Validation of the Synergistic Effect of Multiple Modifications
[0080] Using the γ-Al2O3 and magnesium aluminum hydrotalcite support prepared in this invention, the following four samples were prepared:
[0081]
[0082] Waste oil containing 100 ppm silicon was treated under the same conditions: temperature 150℃, time 2 h, and dosage 5 wt%.
[0083]
[0084] The results showed that single modification was only effective against certain types of silicon-containing contaminants, and all of them had problems such as a small amount of silicate residue or incomplete hydrolysis of silica esters. Triple modification achieved a synergistic effect of "catalytic hydrolysis → chemical fixation → physical retention". When the ratio of γ-Al2O3 to magnesium aluminum hydrotalcite was 3:7, the desilication rate was significantly increased to 97% without increasing the acid value of the oil and having no negative impact on the quality of the oil.
[0085] Example 7: Adaptability to different types of waste oil
[0086] Sample D from Example 6 was used to treat four different types of waste oil:
[0087]
[0088] Processing conditions: batch, addition amount 8 wt%, 160℃, 2.5 h. Results show that this material has good versatility for different types of oils, with a desilication rate consistently above 95%.
[0089] Example 8: Batch Processing Temperature and Time Optimization
[0090] The waste cooking oil from Example 6 was treated with sample D at a dosage of 5 wt%. The effects of temperatures of 80, 120, 150, 180, and 200 °C and times of 0.5, 1, 2, and 3 h on the desiliconization rate were investigated.
[0091] At 80℃ for 2 hours, the desilication rate was only 58%, indicating a slow hydrolysis reaction rate.
[0092] 120℃, 2 h: Desilication rate 85%, basically reaching equilibrium;
[0093] At 150℃ for 1 hour, the desilication rate was 92%, reaching 96% after 1.5 hours and 97% after 2 hours.
[0094] 180℃, 1 h: Desilication rate 93%, but the acid value of the oil increased by 0.8 mg KOH / g;
[0095] 200℃, 0.5 h: Desilication rate 89%, side reactions significantly increased.
[0096] Determine the optimal process window: temperature 120–160℃, time 1.5–2.5 h.
[0097] Example 9: Long-term stability test of fixed bed during continuous operation
[0098] The fixed-bed reactor has an inner diameter of 20 mm and a filling height of 300 mm. It is filled with 50 g of the triple-modified γ-Al₂O₃ and magnesium aluminum hydrotalcite carrier prepared according to this invention, and mixed according to the sample D ratio in Example 6. The reactor treats kitchen waste oil with a silicon content of 90–110 ppm under the following operating conditions: temperature 150℃, liquid hourly space velocity 1.0 h⁻¹. -1 Continuous operation.
[0099]
[0100] The effective operating time is approximately 600 hours, and the cumulative amount of grease processed is approximately 15 L. Analysis of the material discharged after the bed has been penetrated shows that the cumulative adsorption of silicon reaches 35 mg Si / g of material, at which point the desiliconization rate drops to 83%.
[0101] Example 10: Systematic evaluation of material regeneration performance
[0102] The deactivated material from Example 9 after 600 hours of operation was regenerated:
[0103] Alkaline washing: Soak in 0.1 mol / L NaOH solution at room temperature for 2 h, then wash with deionized water until neutral;
[0104] Drying: 120℃, 4 h;
[0105] Activation: N2 atmosphere, 400℃, 2 h.
[0106] Repeat the above "use → regeneration" cycle a total of 5 times, using fresh kitchen waste oil in each cycle, with batch conditions the same as in Example 7.
[0107]
[0108] After 5 cycles, the desilication rate still reached 84%, the specific surface area remained at 84% of the initial value, and the pore structure was basically stable, indicating that the material has good renewability and structural stability.
[0109] Example 11 (Comparison with existing technology)
[0110] The material of the present invention (Sample D of Example 6) was compared in parallel with three existing desilication materials:
[0111]
[0112] Test conditions: Waste cooking oil, initial silicon content 105 ppm, addition amount 5 wt%, 150℃, 2 h. The material of this invention has the highest desiliconization efficiency and does not introduce any silicon element, completely solving the problem of secondary pollution.
[0113] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A non-silicon-based porous adsorption-catalytic coupling material, characterized in that, include: Non-silicon-based host material and functional modification layer; a) The non-silicon-based host material is a calcination product of γ-Al2O3 and magnesium aluminum hydrotalcite; and the surface of the host material has both weak acidic sites and weak basic sites, the weak basic sites of which can promote the hydrolysis of silicon ester compounds. The non-silicon-based host material has a predominantly mesoporous pore structure with a pore size ranging from 5 nm to 20 nm and a specific surface area ≥ 200 m². 2 / g, pore volume ≥0.3 cm³ 3 / g; The density of weakly basic sites on the surface of the main material is 0.1–0.5 mmol / g, and the density of weakly acidic sites is 0.2–0.6 mmol / g. The weakly acidic sites on the surface of the main material originate from the coordinated unsaturated Al in γ-Al2O3 and the calcination products of magnesium aluminum hydrotalcite. 3+ And the interaction between surface Al-OH, surface aluminum ions and hydroxyl groups, the coordinated unsaturated Al 3+ It is a Lewis acid, and the surface Al-OH, the interaction between surface aluminum ions and hydroxyl groups is a Brønsted acid; The weakly basic site comes from Al - O - Mg-OH and O at oxygen vacancies 2- Species; b) A functional modification layer located on the surface and within the pores of the host material, wherein the functional modification layer comprises 5 wt% organic amine, 1.5 mmol / g phosphate groups, and 5 wt% metal ions, and wherein the functional modification layer is silicon-free, and the metal ions are Fe. 3+ ; The organic amine is a non-silane organic amine, and the phosphate group is derived from non-silicon phosphates.
2. A method for preparing a non-silicon-based porous adsorption-catalytic coupling material, characterized in that, Includes the following steps: S1: Preparation of host material γ-Al2O3 S11. Sol preparation Accurately weigh out BASF Pluronic P123 template agent, dissolve it in anhydrous ethanol, and stir at room temperature until completely dissolved. Add concentrated nitric acid (65 wt%) dropwise, stirring until the solution is homogeneous. Add aluminum isopropoxide, aluminum nitrate, or aluminum sulfate to the solution and continue stirring at room temperature to form a clear and transparent sol. The preparation process involves controlling the temperature at 25-30℃ and the stirring speed at 300-400 rpm to ensure that the template agent, acid, and aluminum source come into full contact and form a uniform sol system. S12. Sol aging The obtained transparent sol was transferred into an oven and evaporated at a constant temperature of 40-80℃ for 24-48 hours to form a gel-like composite material powder. The gel powder was then removed and further dried in a vacuum drying oven at 60-80℃ for 12-24 hours to completely remove residual solvent. S13. Firing and shaping The dried raw powder was placed in a muffle furnace and heated at a rate of 1-5 °C / min in an air atmosphere. It was held at 250 °C for 2 h and at 500 °C for 4 h. After calcination, it was naturally cooled to room temperature to obtain a white mesoporous γ-Al2O3 main material. S2. Preparation of the main material, magnesium aluminum hydrotalcite. S21. Preparation of precursor solution Accurately weigh Mg(NO3)2·6H2O and Al(NO3)3·9H2O, mix them in a Mg / Al molar ratio of 3:1, dissolve them in deionized water, and prepare a mixed salt solution with a total metal ion concentration of 1.0 mol / L. For the precipitant solution: dissolve NaOH and Na2CO3 in deionized water to make the NaOH concentration 2.0 mol / L and the Na2CO3 concentration 0.5 mol / L. S22. Synthesis reaction of magnesium aluminum hydrotalcite Under a 60℃ water bath and 600rpm stirring, the metal salt solution and precipitant solution were added dropwise in parallel to the reaction vessel at a rate of 1.5 mL / min. The dropping rate was controlled by a micro-injection pump to keep the pH of the mixed solution strictly at 10±0.
2. After the dropping was completed, the slurry was transferred to a stainless steel high-pressure reactor and statically crystallized at 120℃ for 24 h. S23. Crystallization washing After crystallization, the mixture was cooled to room temperature, centrifuged to separate the precipitate, washed repeatedly with deionized water until the pH of the filtrate was 7, then washed once with anhydrous ethanol, and the precipitate was dried in an oven at 80°C for 12 h to obtain the magnesium aluminum hydrotalcite precursor. S3. Main material firing and molding 1-5 parts of the prepared γ-Al₂O₃ and 3-7 parts of magnesium aluminum hydrotalcite were mixed and placed in a muffle furnace. The temperature was increased to 550℃ at a heating rate of 2℃ / min, and calcined in air for 4 h. After natural cooling, Mg(Al)O composite metal oxide was obtained. The specific surface area was tested to be ≥250 m². 2 / g, with pore sizes mainly distributed in the range of 5–15 nm; the density of weakly basic sites is 0.45–0.50 mmol / g, and the density of weakly acidic sites is 0.3–0.6 mmol / g; S4: Functional Modification Functional modifications are categorized into organic amine modifications, phosphate modifications, and metal ion modifications. S41. Organic amine modification: The main material is dispersed in an anhydrous ethanol solution of an organic amine, refluxed and stirred at 60-80°C for 6-12 h, then filtered, washed and dried. The organic amine is a non-silane organic amine. S42. Phosphate modification: The material is immersed in a 0.1-1 mol / L phosphoric acid solution, stirred at room temperature for 2-6 h, dried, and then heat-treated at 200-300℃. S43. Metal ion modification: The precursor solution is impregnated onto the host material using an equal-volume impregnation method, followed by standing, drying, and calcination at 400–500°C. The metal ion is Fe. 3+ ; S5: Activation treatment The S4-modified material was activated in an inert gas at 300–500 °C for 1–4 hours to obtain the non-silicon-based porous adsorption-catalytic coupling material.
Citation Information
Patent Citations
Liquid hydrocarbon adsorption arsenic removal catalyst and preparation method thereof
CN114377667A
Ni-based'bimetallic-alkali-acid 'multifunctional hydrotalcite catalyst as well as preparation method and application thereof
CN119701967A